Hasil Informal Reasoning (IR) Siswa dalam Pembelajaran Ilmu Pengetahuan Alam - Karmana, I Wayan (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
This article aims to explain the results of students' informal reasoning in learning natural sciences. In various research journals that have been screened, the results obtained are that students already know socio-scientific issues in everyday life. But they have not been able to provide reasoning informally correctly on the issues given.